2008
DOI: 10.1158/0008-5472.can-07-6110
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic MicroRNAs in Stage II Colon Cancer

Abstract: MicroRNAs (miRNA) are a class of small noncoding RNAs with important posttranscriptional regulatory functions. Recent data suggest that miRNAs are aberrantly expressed in many human cancers and that they may play significant roles in carcinogenesis. Here, we used microarrays to profile the expression of 315 human miRNAs in 10 normal mucosa samples and 49 stage II colon cancers differing with regard to microsatellite status and recurrence of disease. Several miRNAs were differentially expressed between normal t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
373
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 456 publications
(414 citation statements)
references
References 43 publications
31
373
3
4
Order By: Relevance
“…Efficient transfection was confirmed by qPCR ( Figure 3a). As expected, miR-126 and miR-145 reduced cell viability (Guo et al, 2008;Schepeler et al, 2008), and interestingly miR-139-5p and miR-30e-3p also inhibited cell viability in a dosage-dependent manner ( Figure 3b). Restriction of cell growth was also evident in a detailed time course experiment (Figure 3c).…”
Section: Wnt Regulation Of Micrornas In Colorectal Cancer T Schepelersupporting
confidence: 78%
See 2 more Smart Citations
“…Efficient transfection was confirmed by qPCR ( Figure 3a). As expected, miR-126 and miR-145 reduced cell viability (Guo et al, 2008;Schepeler et al, 2008), and interestingly miR-139-5p and miR-30e-3p also inhibited cell viability in a dosage-dependent manner ( Figure 3b). Restriction of cell growth was also evident in a detailed time course experiment (Figure 3c).…”
Section: Wnt Regulation Of Micrornas In Colorectal Cancer T Schepelersupporting
confidence: 78%
“…dnTCF4-responsive miRNAs are downregulated in CRC specimens and CRC cell lines Among the numerous miRNAs altered as a consequence of dnTCF4 overexpression, we noticed several of the upregulated miRNAs to have been previously associated with restriction of cancer cell growth (miR449a, (Henson et al, 2009;Noonan et al, 2009;Slaby et al, 2009;Chen et al, 2010;Ding et al, 2010;Ostenfeld et al, 2010). Interestingly, in addition to prominent growth-inhibitory miRNAs commonly downregulated in CRC, such as miR-126 and miR-145 (Guo et al, 2008;Schepeler et al, 2008), several miRNAs with unknown function in CRC cells (for example, miR-574-3p, miR-30e-3p and miR-139-5p) were also upregulated, which prompted us to hypothesize that some of these miRNAs may also be dysregulated in CRC. Accordingly, we examined miRNA expression using the same miRNA TaqMan platform in 46 primary stage II CRCs and 14 adjacent normal mucosa samples.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Although few samples were analyzed, this suggests that DNA hypermethylation could contribute to the reduced expression, although other regulatory mechanisms are most likely also involved. Earlier studies have shown that miR-145 reduces the viability of colon and cervical cancer cells 96 h posttransfection (Shi et al, 2007;Schepeler et al, 2008;Wang et al, 2008) and regulate a quiescent versus proliferative state of smooth muscle cells (Cordes et al, 2009). In this study, we identified miR-145 as an inducer of time-and dose-dependent massive cell death with classical apoptotic features, such as caspase activation, fragmentation and compact condensation of the chromatin, and plasma membrane blebbing.…”
Section: Discussionmentioning
confidence: 64%
“…In situ hybridization (ISH) analysis has identified miR-145 expression in myoepithelial cells of the mammary lobules and ducts as well as in smooth muscle cells (Sempere et al, 2007;Cordes et al, 2009). Furthermore, studies have shown that miR-145 reduces cell viability in colon and cervical cancer cell lines after prolonged exposure (Shi et al, 2007;Schepeler et al, 2008;Wang et al, 2008). Finally, the expression of miR-145 has been shown to be induced by p53 (Sachdeva et al, 2009) and regulated by an enhancer element activated by SRF and Nkx-2 transcription factors (Cordes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%